Vaccine as a treatment for gonorrhea and its main impasses - Fagundes, Thaylisson Davi Silva; Priscinotte, Marcela Souza Carvalho da Costa; Ribeiro, Alinne Lima Fernandes; Dotto, Paulo Henrique Flores; Fogaça, Marcus Vinícius Tavares; Muszkat, Victória Jorge; Moreira, Kamile Maria Saboia; Galvão, Daniel Studart Corrêa; Veloso, Pedro Henrique de Azevedo; Neto, Luiz José da Rocha; Miranda, Guilherme Silva; Santana, Milena Alves; et al. (Seven Editora, 2024)
INTRODUCTION: Gonorrhea is a disease caused by the bacterium Neisseria gonorrhoeae, it is a sexually transmitted infection, which manifests itself between men and women, with varied symptoms, therefore, for the diagnosis it is necessary microscopic examinations, cultures or nucleic acid amplification tests and regarding the treatment, its first line is the association of ceftriaxone with azithromycin. METHODOLOGY: This is a literature review, whose databases were taken from the SciELO and PubMed data platforms. The research period was from July 2023, meeting the inclusion criteria, which were articles from the years 2000 to 2023, in Portuguese and English, online texts, and in full texts. The following health descriptors (DeCS) were used as strategies for better evaluation of the texts: "Treatment", "Gonorrhea" and "Vaccine". DISCUSSION: The bacterium Neisseria gonorrhoeae is responsible for the sexually transmitted infection (STI) known as gonorrhea. Gonorrhea can manifest as urethritis in men, cervicitis, or urethritis in women, and can also affect extragenital sites such as the pharynx, rectum, conjunctiva, and, in rare cases, systemically, in both sexes. Confirmation of the diagnosis requires microscopic examinations of Gram-stained specimens, bacterial cultures, or nucleic acid amplification tests. The recommended first-line treatment is single-dose systemic therapy, usually with injectable ceftriaxone and oral azithromycin. However, a major public health concern on a global scale is the emergence of high levels of antimicrobial resistance (AMR) in N. gonorrhoeae, which compromises the effectiveness of available treatments for gonorrhea. Neisseria gonorrhoeae has been a historical challenge for vaccine development, due to the expression of variable surface molecules and its ability to cause repeated infections without inducing protective immunity. Current control measures are clearly insufficient and are threatened by the rapid emergence of antibiotic resistance. Currently, gonorrhea is considered a "superbug" as there is no reliable monotherapy for empirical treatment. Antibiotic resistance has increased treatment costs and led to the need for surveillance programs to track the spread of resistant strains. FINAL COMMENTS: Thus, it is extremely important to start discussions about alternative treatments for diseases caused by bacteria and viruses, without a preventive treatment specified yet. In the case of gonorrhea, it is interesting to study more and more, studying the possibilities and main factors about the obstacles to the creation of the vaccine. DOI:https://doi.org/10.56238/sevened2024.025-006